2022
DOI: 10.1212/wnl.0000000000200511
|View full text |Cite
|
Sign up to set email alerts
|

Brain Sagging Dementia—Diagnosis, Treatment, and Outcome

Abstract: Brain sagging dementia (BSD), caused by spontaneous intracranial hypotension (SIH), is a rare syndrome that is only recently recognized, mimicking the clinical findings of behavioral variant frontotemporal dementia (bvFTD). Being aware of its signs and symptoms is essential for early diagnosis and treatment in this potentially reversible form of dementia. Our objective was to identify cases with BSD in the literature and present its clinical characteristics, diagnostic workup, treatment options, and outcome.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…The constellation of signs and symptoms of frontotemporal dementia caused by SIH, known as brain sagging dementia (BSD), has been increasingly recognized recently ( 7 9 ). The condition is twice as common in male patients and peaks in the sixth decade of life ( 3 ). Like in SIH, most patients present with some form of headache.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The constellation of signs and symptoms of frontotemporal dementia caused by SIH, known as brain sagging dementia (BSD), has been increasingly recognized recently ( 7 9 ). The condition is twice as common in male patients and peaks in the sixth decade of life ( 3 ). Like in SIH, most patients present with some form of headache.…”
Section: Discussionmentioning
confidence: 99%
“…Although a spinal CSF leakage is thought to be the etiology behind SIH and BSD, it is not radiologically evident in a significant number of patients ( 3 , 4 ). In a recent review on BSD, a CSF leakage site was found in merely 13% of cases ( 3 ). Moreover, no cranial leak was reported in the two largest reviews on SIH and BSD ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations